2006
DOI: 10.1210/jc.2005-1766
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroids and the Periosteum—Reconsidering the Roles of Androgens and Estrogens in Periosteal Expansion

Abstract: Simple concepts of the roles of sex steroids in periosteal apposition have to be reconsidered in the context of these recent findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(97 citation statements)
references
References 54 publications
7
87
1
2
Order By: Relevance
“…Following the mechanostat theory, the considerable increase in muscle mass imposes a higher strain on bone which stimulates higher bone modeling and remodeling (25). Indeed, muscle mass constitutes one of the main triggers in periosteal bone formation during puberty (6,25,26), and a beneficial effect of structured exercise in premenopausal women on femoral neck and lumbar spine aBMD was demonstrated in a recent (27). In some of these trials, the training indeed promoted bone formation (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the mechanostat theory, the considerable increase in muscle mass imposes a higher strain on bone which stimulates higher bone modeling and remodeling (25). Indeed, muscle mass constitutes one of the main triggers in periosteal bone formation during puberty (6,25,26), and a beneficial effect of structured exercise in premenopausal women on femoral neck and lumbar spine aBMD was demonstrated in a recent (27). In some of these trials, the training indeed promoted bone formation (28).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, quantitative computed tomography (QCT) and visualizing bone geometry can contribute for unraveling the interactions of sex steroid with trabecular and cortical bone. Sex steroids also influence bone size: men develop larger periosteal (outer) and endosteal (inner) circumference than women, partly due to the interplay of sex steroids, mechanical loading, and the growth hormone (GH)/ insulin-like growth factor 1 (IGF1)-axis during puberty (4,5,6). In adulthood, periosteal apposition continues, but at a slower rate in women than in men (7).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, participants in all studies had received varying amounts of GH and androgen therapy, which have both been shown to affect bone health. (39)(40)(41)(42) Therefore, these discrepancies in age and prior drug exposure may affect findings and complicate between-study comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Factors influencing cell phenotype include sex steroids [41,43], endogenous growth factors [26,45] and mechanical loading environment in vivo [27,42], and isolation [30], culture methods [8,13,20,31,37] and the donor site [14] in vitro. Lim [24] identified potential precursor populations within periosteal cultures.…”
Section: Introductionmentioning
confidence: 99%